ANALYSIS OF THE ECONOMIC INDICATORS OF THE MEDICINAL PLANT RESOURCE BASE AND PROCESSING ACTIVITIES IN UZBEKISTAN - Usmonov Mirg‘ulom Xoshim og‘li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This study examines the current state, development trends, and economic, social, and ecological significance of medicinal plant cultivation and processing in Uzbekistan. The country possesses rich natural flora, with hundreds of medicinal and aromatic plant species widely used in healthcare, pharmaceuticals, cosmetics, and food industries. The research analyzes the raw material base of medicinal plants, their role in public health improvement, employment generation, and export development. Special attention is given to processing efficiency, value addition, and the importance of standardization and quality control in enhancing competitiveness in international markets. The study also highlights existing challenges, including limited processing capacity and unequal distribution of added value, while emphasizing the need for investment in research, modern technologies, and market expansion. The findings confirm that the intensive development of medicinal plant cultivation and processing can significantly contribute to sustainable economic growth, environmental protection, and the strengthening of Uzbekistan’s agricultural and pharmaceutical sectors.